Evaluation of samples of the coarse aggregate from concrete wates to produce new concrete - Cruz Zuñiga, Nidia (2025)
The demands for construction materials are increasing, their sources are scarce and the management of construction and demolition waste is very complex. The research that supported this article sought to study the characteristics of coarse aggregate for construction from civil works waste, and compare them with traditional virgin aggregates, in order to assess their possible use. We worked with three sources of raw material for recycling: masonry walls, precast tiles, and cast-in-place concrete (test cylinders); all facilitated by the LanammeUCR. The standards established by INTECO were followed, both for the characterization of the recycled aggregates and for the mix designs. Three different percentages of recycled coarse aggregate were used in the mixtures, substituting the natural one. The results showed small variations regarding the behavior of the virgin aggregate, especially in absorption, unit weight and wear. Very favorable results were obtained in terms of the compressive strength of the concretes with recycled coarse aggregate, always contemplating a mix design that adjusted to its characteristics. Among the limitations is that the durability of manufactured concrete was not studied; recycled fine aggregate was not used either. Both phenomena will be addressed in future research. At the end of the investigation, it is concluded that the recycling of coarse aggregate is technically feasible.